Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Determine the mean of the numbers a, b, c, and d. - System of equations.?
Alex chooses four numbers. a, b, c, and d. For each of the numbers, he determines the sum of the numbers and the mean of the other three. He gets the following sums 60, 64, 68, and 72. Determine the mean of the numbers a, b, c, and d.
I need to solve this problem by using System of equations. How can I solve this? Can someone show me step by step. I really want to learn.
I know that the answer is going to be 33.
Thank you.
2 Answers
- ?Lv 75 months ago
Find:
Mean = (a + b + c + d) / 4 = ?
From the problem description:
a + (b + c + d) / 3 = x₁
b + (a + c + d) / 3 = x₂
c + (a + b + d) / 3 = x₃
d + (a + b + c) / 3 = x₄
We know the numbers x₁ through x₄, but not exactly which is which, but we do know that:
x₁ + x₂ + x₃ + x₄ = 60 + 64 + 68 + 72
Distribute:
a + (1/3)b + (1/3)c + (1/3)d = x₁
b + (1/3)a + (1/3)c + (1/3)d = x₂
c + (1/3)a + (1/3)b + (1/3)d = x₃
d + (1/3)a + (1/3)b + (1/3)c = x₄
Add all equations together:
a + (1/3)b + (1/3)c + (1/3)d + b + (1/3)a + (1/3)c + (1/3)d + c + (1/3)a + (1/3)b + (1/3)d + d + (1/3)a + (1/3)b + (1/3)c = 60 + 64 + 68 + 72
a + b + c + d + a + b + c + d = 60 + 64 + 68 + 72
2(a + b + c + d) = 60 + 64 + 68 + 72
a + b + c + d = (60 + 64 + 68 + 72) / 2
Substitute this result into the mean:
(a + b + c + d) / 4 = [(60 + 64 + 68 + 72) / 2] / 4
Mean = (60 + 64 + 68 + 72) / 8
Mean = 33
- llafferLv 75 months ago
If you add "a" plus the mean of the other three, you get 60.
If you add "b" plus the mean of the other three, you get 64, etc.
So writing these as a system of four equations and four unknowns we get:
a + (b + c + d) / 3 = 60
b + (a + c + d) / 3 = 64
c + (a + b + d) / 3 = 68
d + (a + b + c) / 3 = 72
And you want to know the mean of all 4 numbers:
(a + b + c + d) / 4
Let's start out by multiplying all four equations by 3 to get rid of the fractions:
a + (b + c + d) / 3 = 60 and b + (a + c + d) / 3 = 64 and c + (a + b + d) / 3 = 68 and d + (a + b + c) / 3 = 72
3a + b + c + d = 180 and 3b + a + c + d = 192 and 3c + a + b + d = 204 and 3d + a + b + c = 216
Now I'll solve the last equation for a in terms of the other three then substitute into the other three equations:
3d + a + b + c = 216
a = 216 - b - c - 3d
3a + b + c + d = 180 and 3b + a + c + d = 192 and 3c + a + b + d = 204
3(216 - b - c - 3d) + b + c + d = 180 and 3b + 216 - b - c - 3d + c + d = 192 and 3c + 216 - b - c - 3d + b + d = 204
Now simplify:
648 - 3b - 3c - 9d + b + c + d = 180 and 2b - 2d = -24 and 2c - 2d = -12
We actually had additional terms cancel out in the second and third equations which make things easier. We can continue to simplify the last two by dividing both sides by 2 as we simplify the first one further:
-2b - 2c - 8d = -468 and b - d = -12 and c - d = -6
I'll simplify the first equation by dividing both sides by -2 and solve the second equation for b in terms of d:
b + c + 4d = 234 and b = d - 12 and c - d = -6
Now we can substitute the expression for b in terms of d into the other two equations:
b + c + 4d = 234 and c - d = -6
d - 12 + c + 4d = 234 and c - d = -6
c + 5d = 246 and c - d = -6
Solve the last equation for c in terms of d and substitute again:
c - d = -6
c = d - 6
c + 5d = 246
d - 6 + 5d = 246
6d = 252
d = 42
Now that we know d we can start working back and solve for the others:
b = d - 12 and c = d - 6
b = 42 - 12 and c = 42 - 6
b = 30 and c = 36
a = 216 - b - c - 3d
a = 216 - 30 - 36 - 3(42)
a = 216 - 30 - 36 - 126
a = 24
Now we have the four numbers we can find the mean:
(a + b + c + d) / 4
(24 + 30 + 36 + 42) / 4
132 / 4
33 is the mean of your four numbers.